Sports Infrastructure and Leadership Support on Sport Participation Frequency - Utami Yerikania (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. The goal of this research was to see how leadership support for sports infrastructure affected the frequency with which people participated in sports. Materials and methods. Tests and observations were used as data collecting strategies. The data was descriptively and qualitatively examined. Results. The study's findings demonstrate that while Pahlawan University's infrastructure does not meet all of the requirements, it is already usable. Conclusions. Although there is leadership support, it is still insufficient, causing current participants to underutilize existing infrastructure owing to the civitas' hectic working hours.